Charpy impact toughness and transition temperature in ferrite–perlite steel - Rodríguez Baracaldo, Rodolfo; Cubides Herrera, Cristian Sebastián; VILLALBA RONDÓN, DIEGO ALEJANDRO (Scientia et Technica, 2019)
Charpy V-notch impact tests on 10 mm thick, Dual-Phase ferrite-perlite steel were evaluated at temperatures ranging from 90 ºC to -60 ºC. Fracture surfaces were analysed by optical microscope (OM). Due to the high dispersion, showed in the results, numerous tests under the same conditions and the use of statistical methods are needed to obtain a reliable value. The transition temperature calculated (45 ºC) and Charpy impact toughness was analysed in function of microstructure and carbon equivalent.